Characterization of polymethylmethacrylate microspheres loaded with silver and doxycycline for dental materials applications. Issue 6 (June 2022) - De Morais, Dayana C.; Jackson, John K.; Kong, Jong Hoon; Ghaffari, Sahand; Palma-Dibb, Regina G.; Carvalho, Ricardo M.; Lange, Dirk; Manso, Adriana P.
Highlights: Manufacturing of PMMA microspheres doped with antibacterial drugs. Efficient and continuous release of antibacterial drugs from PMMA microspheres. Antibacterial activity of drug-loaded PMMA microspheres against S. mutans . Addition of PMMA microspheres into Glass Ionomer Cements (GICs). Antibacterial activity of GICs loaded with PMMA microspheres against S. mutans . Abstract: Objectives: The manufacturing of polymethylmethacrylate(PMMA) microspheres loaded with doxycycline(DOX) and/or silver sulfate(Ag2 SO4 ) to be incorporated into glass ionomer cement(GIC). Methods: PMMA microspheres were manufactured with Ag2 SO4 (1–5%) and/or DOX(5–15%). Particle size, encapsulation efficiency and drug release were measured by light microscope, ICP, and HPLC. Microspheres were added to a dental GIC(20%w/w). Drug release and DTS were investigated. Minimum inhibitory concentration and antibacterial effects of PMMA microspheres into GIC materials were tested. Results: The median diameter of 50 µm was obtained for microspheres. DOX was encapsulated at an efficiency of 8.3% using a theoretical loading of 15%DOX + 5%Ag2 SO4 . The Ag2 SO4 encapsulation efficiency was 0.63% using a theoretical loading of 5%AgSO4 . All groups showed burst release within the first day and continued released up to 15 days, with 60–83% of DOX and approximately 30% of silver. For GIC, approximately 15% of DOX and 0.18% of silver were released in a 7-day period. Microbiological results showed an antimicrobial effect against S. mutans when the lead formulation of microspheres was added. The DTS was reduced by the inclusion of microspheres. Significance: PMMA microspheres containing DOX and Ag2 SO4 offer a sustained antimicrobial activity for dental applications and promising potential for the biomedical field.